Harnessing magnetic cross-linked cell aggregates (CLCAs) for cost-effective preparation of Konjac mannan-oligosaccharide - Baoyu Cui; Haiqiang Lu; Xue Liu; Yiran Zhang; Xinxi Gu (Microbial Cell Factories, 2025)
Abstract Konjac mannan oligosaccharides (KMOS) are currently popular in food additives for their health benefits. However, the simple and efficient preparation of KMOS is still a challenge. In this study, A novel gene encoding β-mannanase (CsMan134) from Cellvibrio sp. KY-GH-1 was displayed on the surface of E. coli cells. Subsequently, E.coli cells (3 g/L) expressing the mannanase CsMan134 were immobilized using 8% (w/v) polyvinyl alcohol, 3% (w/v) sodium alginate, and 3.5% (w/v) Fe₃O₄ to construct magnetic cross-linked cell aggregates (mag-CLCAs). The mannanase CsMan134 demonstrated the highest catalytic efficiency towards konjac mannan compared to other mannans. Compared to free enzyme, the mag-CLCAs exhibited enhanced enzymatic activity across a range of temperatures and pH levels. Furthermore, the mag-CLCAs showed improved thermal stability, retaining over 80% of its initial activity after heating at 50 °C for 180 min, whereas the free enzyme retained only 50% of its residual activity. Scanning electron microscopy (SEM) and vibrating sample magnetometry (VSM) analyses indicated that the mag-CLCAs also maintained good operational stability, retaining more than 75% of their initial activity over five cycles. The mag-CLCAs were effective in converting konjac mannan into a substantial amount of oligosaccharides with a degree of polymerization (DP) of 2–4. In conclusion, the mag-CLCAs represent a valuable, efficient, and cost-effective biocatalyst for the production of KMOS for industrial applications.